The Thought Construction of Yusuf al-Qaradhawi in Understanding The Hadith: An Analysis of Non-Fixed Variable and Fixed Means of Achieving Fixed Goals - Muhammad Alfreda Daib Insan Labib (Universiti Sains Islam Malaysia, 2024)
Journal of Hadith Studies Volume 9 Issue 1 Page (100-109)